Genetic diversity and population structure of grewia nervosa (lour.) Panigrahi from Gazipur and Cumilla sal forests, Bangladesh (Bangladesh Journal of Botany, 2024)
The study was carried out to determine the genetic diversity and population structure of a medicinal plant Grewia nervosa (Lour.) Panigrahi from two different regions of Sal forest,  one from Cumilla showed more abundance than Sal plant and Gazipur showed relatively less abundance of it. Interest was taken to find out the best genotypes for breeding and conservation program. With these purposes 10 RAPD and 7 ISSR loci were used in the present investigation. Populations from Cumilla Sal forest showed significantly higher polymorphism and comparatively higher heterozygosity than that of Gazipur. Very low gene flow and high differentiation among the populations was noticed in  Gazipur Sal forest  whereas moderate gene flow and less differentiation of  populations of Cumilla.Bangladesh J. Bot. 53(4): 991-999, 2024 (December)